2008
DOI: 10.15288/jsad.2008.69.561
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Individuals Screening Positive for Substance Use in a Welfare Setting: Implications for Welfare and Substance-Use Disorders Treatment Systems

Abstract: Objective-This study examined barriers to employability, motivation to abstain from substances and to work, and involvement in multiple service systems among male and female welfare applicants with alcohol-and drug-use problems.Method-A representative sample (N = 1,431) of all persons applying for public assistance who screened positive for substance involvement over a 2-year period in a large urban county were recruited in welfare offices. Legal, education, general health, mental health, employment, housing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…in this second study, we compared coordinated care management (ccM) with the referral and monitoring activities of usual care (uc) within the human Resources administration. in a first study reporting on suD treatment participation and abstinence outcomes for this sample, we found that ccM was more effective than uc, except for clients receiving methadone maintenance at baseline (Morgenstern et al, 2009a).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…in this second study, we compared coordinated care management (ccM) with the referral and monitoring activities of usual care (uc) within the human Resources administration. in a first study reporting on suD treatment participation and abstinence outcomes for this sample, we found that ccM was more effective than uc, except for clients receiving methadone maintenance at baseline (Morgenstern et al, 2009a).…”
mentioning
confidence: 56%
“…Days of employment were assessed using a structured interview measuring the number of days worked since the previous assessment time point. the interview, previously used in the multisite employment Retention and advancement (eRa) evaluation of innovative welfare programs for hard-to-employ populations sponsored by the Department of health and human services, is a state-of-the-art measure of employment outcomes in welfare-to-work evaluations (MDRc, 2008). at each follow-up assessment, participants were asked to recall how many days since the last interview they were paid for working on the books, off the books, in full-time jobs, or in part-time jobs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations